Estrutura eletrônica de anéis quânticos - Oliveira Neto, Vivaldo Lopes (Universidade Federal de São Carlos, 2011)
The nanoscopic structures with ring topology, or quantum rings, have attracted the interest due to their unique rotational symmetry and the possibility of checking fundamental quantum phenomena. Among them, the study of Aharonov-Bohm interference effects appears with special emphasis. Analytical calculations of the electronic structure of quantum rings were performed for the electron confined in one-dimensional and threedimensional potentials. These calculations were complemented by the electronic structure simulation of the valence band using the k.p method, main objective this work. This theoretical contribution is a part of a collaboration with experimental groups of growth and spectroscopy which deal with problems related to the manipulation of electronic states and spin properties of quantum rings. The ground states of both electrons and holes in quantum dots (quasi-zero-dimensional systems) have zero angular momentum (in the absence of magnetic fields and low fields) and exhibit a diamagnetic response of the spin states in the presence of an external magnetic field. In non-magnetic quantum dots, the spin properties are mainly attributed to the electron spin and the heavy hole. On the other hand, it is assumed that the light holes have a minor role in the properties of the exciton ground state. Our results show that the interband coupling may lead to the angular momentum hybridization of the electronic states, even in the ground state and the the light hole may assume a relevant role. The adaptation and improvement of calculations of the electronic structure using the k.p methods were two of the main objectives of this work. The theoretical tools developed aim to contribute to the establishment of protocols for optimal use and application of such systems.
Keywords: Física do estado sólido; Matéria condensada; Método k.p; Estrutura eletrônica; Anéis quânticos; Quantum rings; K.P method; Electronic structure; CIENCIAS EXATAS E DA TERRA::FISICA